Nurses’ perceptions on nursing supervision in Primary Health Care - Farah, Beatriz Francisco; Dutra, Herica Silva; Ramos, Ana Cecília Thamer Miranda; Friedrich, Denise Barbosa de Castro (Rev Rene, 2016)
Objective: to understand the perceptions of nurses on nursing supervision in the work process. Methods: this is a qualitative research, with a semi-structured interview, performed with 16 nurses. Data analysis was performed through content analysis. Results: two meanings topics emerged from the speeches of the participants: Nurses´ activities in Primary Health Care Units and Nurses´ perceptions about nursing supervision. In the first category, the actions listed were filling out forms and reports under the supervision of the nursing service. In the second category, supervision was perceived as a function of management and follow-up of the activities planned by the team, in opposition to the classical supervision concept, which is inspecting. Conclusion: nursing supervision has been configured for primary care nurses as an administrative function that involves planning, organization, coordination, evaluation, follow-up and support for the health team.